Perangkat Lunak Pengelolaan Rekam Medis Bayi Baru Lahir (Studi Kasus Rumah Sakit Panti Waluyo Surakarta) - Nurhayati, Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
The management of newborn medical records in hospitals has an important role in generating birth history information, identification of infants and the condition of the baby when born. Panti Waluyo Hospital Surakarta is one of the hospitals that became the reference of labor in the city of Surakarta. Recording of medical records of infant identification and perinatology assessment is still done manually and constrained record quality on the form that causes the reduced value of information from newborns. It is therefore necessary to establish a newborn medical record management software covering infant identification, perinatological assessment and birth certificate to support the accuracy and speed of management of newborn data. This research method includes problem identification, data collection and software development. Software development methods using System Development Life Cycle (SDLC) include Project Identification and Selection, Initiation and Project Planning, Design Stage, Implementation, and Maintenance. This research produces newborn medical record management software consisting of patient data, paramedical data, ward data, diagnostic data, medical action data, infant identification data management, perinatalogi assessment data management and birth certificate. The conclusion of this research is the software has been able to perform data management of newborn medical record, especially baby identification, perinatology and birth certificate quickly and accurately so as to facilitate medical record unit to manage infant birth data information in order to support optimal medical recorder service. Keywords : newborns, medical records, identification of newborns